2006
DOI: 10.1002/jor.20080
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of porcine small intestine submucosa on the healing of medial collateral ligament: A functional tissue engineering study

Abstract: Porcine small intestinal submucosa (SIS) was previously shown to enhance the mechanical properties of healing medial collateral ligaments (MCL), and the histomorphological appearance and collagen type V/I ratio were found to be close to those of normal MCL. We hypothesized that at a longer term, 26 weeks, SIS could guide a better organized neo-ligament formation, increasing mechanical properties and increasing collagen fibril diameters mediated by a reduction in collagen type V. A 6 mm gap injury in the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 33 publications
2
59
0
2
Order By: Relevance
“…[17][18][19] Several studies have shown that SIS can provide a collagenous matrix to promote cell migration into the healing site to enhance revascularization and repair. [20][21][22][23][24] It is hypothesized that SIS enhance and promote the healing of the ACL. Instead of using the SIS as a load-bearing 10-layered bioscaffold, like in the rotator cuff repair, only a single layer of SIS was used to recruit sufficient healing cells to the hypocellular ACL.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Several studies have shown that SIS can provide a collagenous matrix to promote cell migration into the healing site to enhance revascularization and repair. [20][21][22][23][24] It is hypothesized that SIS enhance and promote the healing of the ACL. Instead of using the SIS as a load-bearing 10-layered bioscaffold, like in the rotator cuff repair, only a single layer of SIS was used to recruit sufficient healing cells to the hypocellular ACL.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid remodelling response can occur once infiltrating host cells selforganise and begin producing their own ECM. This results in a time dependent return to expected mechanical strength and site-appropriate mechanical behaviour after xenogenic implantation (S. , Liang et al 2006.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…25,26 When a single layer of SIS was applied to a gap injury of the rabbit medial collateral ligament (MCL), the healing ligament had better collagen fiber alignment with larger collagen fibril diameters. 22,23 Also, the mechanical properties of the healing MCL were significantly improved with a 33% increase in tangent modulus and a 50% increase in tensile strength.…”
Section: Introductionmentioning
confidence: 98%
“…[16][17][18] An extracellular matrix derived bioscaffold, namely the porcine small intestinal submucosa (SIS), has been successfully used to enhance the repair of ligaments and tendons. [19][20][21][22][23] SIS possesses unique properties including a preferentially aligned collagen type I matrix which is thought to provide contact guidance for the healing cells. Additionally, SIS contains a variety of growth factors capable of attracting healing cells through chemotaxis.…”
Section: Introductionmentioning
confidence: 99%